EOSINOPENIA DAN PROCALCITONIN DALAM SEPSIS - Danny Luhulima; W. Hidayati; IGAAP. Sri Rejeki; R. Permatasari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Sepsis is one of the common causes of morbidity and mortality in the ICU. Clinicians need to know and realize of good diagnosticmarkers to identify sepsis as early as possible. The role of eosinopenia as a marker of sepsis has recently been evaluated.The aim of thisstudy was to test the value of eosinopenia as a diagnostic marker of sepsis in comparison to Procalcitonin. A cross sectional study wasperformed in 61 adult patients with SIRS, and blood of all patients were cultured. Further examinations were done for comparing theeosinophil count with the Procalcitonin levels if the blood culture was positive or when there were clinical signs which supported for sepsis.In this study there were fourty two patients enrolled. Procalcitonin level yielded a sensitivity of 90.0%, specificity of 83.3%, a positivepredictive value (PPV) of 93.1% and a negative predictive value (NPV) of 76.9% at cut-off value of 2.75 ng/mL. The eosinophil (cut off ≤50 cells/μL) produced a sensitivity of 80.0%, specificity of 75.0%, PPV of 88.9%, and NPV of 60.0%. based on this study Procalcitoninappeared to be a more accurate diagnostic of sepsis than eosinopenia, but eosinopenia is still a helpful tool for clinicians, and may also beused as a diagnostic marker of sepsis, because it is highly sensitive, moderately specific, easy to measure, rapid and inexpensive as well.